Peasants’ Land Rights Claims Over Plantation Companies’ Sites in Central Java, Indonesia (1998-2014) - Herwati, Siti Rakhma Mary; Sumarlan, Yanuar (Indonesia Law Review, 2016)
This article reveals the opening of political and legal opportunities for the landless peasants of Central Java at the end of the 1990s to reclaim their lands that were confiscated during the end of the 1950s through a nationalization program to take over Dutch-controlled lands. Taking two sites of plantations that have been targeted as the peasantries’ land reclaiming campaign, this article shows the processes of the reclaiming, the responses of both plantation companies and state, and the respect of the state over rights to access to lands or property rights of the peasants as citizens. Using some legal and anthropological approaches, this article finds that the state—through its apparatuses in business units, legal enforcement agencies, government units, courts, etc—is trapped in a Stocksian Paradox that is worse than its original Latin American version because the state has a deep conflict of interest as one of the “counter-claimants” of the indigenous or peasantries’ claim to rights to property/land. The authors recommend that although a robust civil society representing the peasantries is one of important parts in rights-reclaiming campaigns, the deeper Stocksian Paradox remains the biggest stumbling block in fulfilling state’s roles as rights-givers to its citizens.